Emerging Enterobacteriaceae Infections: Antibiotic Resistance and Novel Treatment Options - Ghassan M. Matar (Frontiers Research Topics, 2017)
Enterobacteriaceae are spread worldwide and the diseases they cause may be fatal especially in immunocompromised patients. Moreover, the high prevalence of ESBL producing Salmonella and Shigella species diseases worldwide suggests major underlying safety issues. According to the World Health Organization (WHO), 2015, approximately 220 million children contract diarrhoeal diseases every year and 96 000 die. As a result, the increase in single or multi drug-resistant foodborne bacterial pathogens is of major public health concern. Moreover, resistance to antimicrobials was found among Salmonella spp and Campylobacter spp from animals and food, and since fluoroquinolones became licensed for use in animal foods, especially for poultry, the rate of fluoroquinolone resistant Salmonella spp and Campylobacter spp in animals and human food, and then in human infections, rapidly increased. To that purpose, the findings of the conducted studies in the book chapters, 1) highlight surveillance studies reporting the occurrence and distribution of resistance to antimicrobial agents, namely, to third generation cephalosporins, carbapenems and fluoroquinolones, 2) describe the mechanisms of transmission of resistance determinants from animals, food products and clinical specimens, that allow implementation of appropriate measures to control their spread and adopt appropriate therapeutic measures, and 3) provide treatment options, useful to medical practice.